Surface Enhanced Raman Spectroscopy and Quantum Chemical Studies on Iminodiacetic Acid Single Crystals. Issue 4 (4th July 2018) - Parameswari, A.; Hussain, Shamima; Premkumar, R.; Mohamed Asath, R.; Franklin Benial, A. Milton
Abstract: Adsorption behaviour of iminodiacetic acid (IDA) on silver surface were investigated based on surface enhanced Raman spectroscopy (SERS) technique and density functional theory calculations. The single crystals of IDA were grown by slow evaporation method and characterized by powder X-ray diffraction (XRD), dynamic light scattering and scanning electron microscopy techniques. Silver nanoparticles (AgNPs) were prepared by solution combustion method using ananas comosus fruit extract as reducing agent. The AgNPs were characterized by powder XRD and high-resolution transmission electron microscopy techniques. Raman and SERS frequencies were analyzed on the basis of potential energy distribution calculation and compared with the experimental values. The structural parameters of IDA molecule was compared with the experimental values. In frontier molecular orbital analysis, the band gap value was significantly reduced for IDA after adsorption on the silver surface indicates the charge transfer associated with the process of adsorption. The redistribution of electrostatic potential and the reduction in band gap after adsorption on silver surface of IDA, reveals its utility in the design of electro active organic molecular devices. SERS spectral analysis reveals that the IDA adsorbed as a tilted orientation on the silver surface. Localization of electron density and the reduction in band gap after adsorption of silver nanoparticles pave the way for designing the electro active organic molecular devices.